Cytokine Release Syndrome Is an Independent Risk Factor Associated With Platelet Transfusion Refractoriness After CAR-T Therapy for Relapsed/Refractory Acute Lymphoblastic Leukemia - Liu, Yadan; Liang, Bin; Liu, Yan; Wei, Guoqing; Wu, Wenjun; Yang, Luxin; Yang, Li; Huang, He; Xie, Jue; Hu, Yongxian (Frontiers in Pharmacology, 2021)
Background: Chimeric antigen receptor T cell (CAR-T) therapy is successful in improving treatment outcomes for relapsed/refractory acute lymphoblastic leukemia (R/R ALL). However, toxicities associated with CAR-T therapy are being increasingly identified. Pancytopenia is one of the most common complications after CAR-T therapy, and platelet transfusions are an essential part of its supportive care. Study Design and Methods: This study aimed to assess the effectiveness of platelet transfusions for R/R ALL patients at our single center and identify associated risk factors. Overall, 44 R/R ALL patients were enrolled in this study, of whom 26 received CAR-T therapy and 18 received salvage chemotherapy. Result: Patients in the CAR-T group had a higher incidence of platelet transfusion refractoriness (PTR) (15/26, 57.7%) than those in the chemotherapy group (3/18, 16.7%) (p = 0.007). For patients receiving CAR-T therapy, multivariate analysis showed that the grade of cytokine release syndrome (CRS) was the only independent risk factor associated with PTR (p = 0.007). Moreover, higher peak serum IL-6 and IFN-γ levels suggested a higher risk of PTR (p = 0.024 and 0.009, respectively). Patients with PTR received more platelet infusion doses than those without PTR (p = 0.0426). Patients with PTR had more grade 3–4 bleeding events than those without PTR (21.4 vs. 0%, p = 0.230), and the cumulative incidence of grade 3–4 bleeding event was different (p = 0.023). Conclusion: We found for the first time that PTR is associated with the CRS grade. Improved knowledge on the mechanisms of PTR after CAR-T therapy is needed to design a rational therapeutic strategy that aims to improve the efficiency of transfusions.